Global burden of blindness or visually impairment attributable to diabetic retinopathy in the adults aged 70 years and older, 1990–2021: Results from the global burden of disease study in 2021 - Chen, Yue; Tang, Songwen; Huang, Yanrui; Deng, Jinmei; Chen, Xueying; Qi, Yuqing; Xiao, Haipeng; Li, Yanbing; Li, Hai; Guan, Hongyu (Diabetes research and clinical practice, 2025)
This study aimed to assess the global burden of vision loss due to diabetic retinopathy (DR) among adults aged 70 and older from 1990 to 2021, focusing on regional, national, gender disparities, and its association with the socio-demographic index (SDI), using Global Burden of Disease (GBD) 2021 data. We analyzed GBD 2021 data to evaluate the prevalence, years lived with disability (YLDs), and trends in DR-related vision loss. Analyses were stratified by region, country, gender, and age. The association between SDI and DR burden was explored, and estimated annual percentage changes (EAPCs) were calculated to assess temporal trends. Between 1990 and 2021, the global burden of DR-related vision loss and YLDs increased steadily, with females disproportionately affected. In 2021, the global prevalence of DR-related blindness reached 401,260 cases. The burden was highest in East Asia, Western Europe, and South Asia. DR burden increased with age and SDI. India reported the most blindness cases, while China had the highest numbers of moderate and severe vision loss. DR-related vision loss among older adults is rising globally, with clear regional and gender disparities. Targeted strategies are essential to mitigate this burden in aging populations.